(untitled) (World Bulletin of Education and Learning, 2025)
Artificial intelligence-based digital games have emerged as an innovative tool in preschool education, offering new opportunities to enhance learning, cognitive development, and social interaction among young children. These technologies allow personalized learning experiences by adapting activities to each child’s developmental level, interests, and pace. Through engaging visual and auditory stimuli, AI-driven games support attention, memory, problem-solving, and early literacy and numeracy skills. They also provide real-time feedback and assessment, enabling educators to monitor progress and identify individual needs more effectively. The integration of AI in preschool game-based learning environments can encourage creativity and independent exploration while maintaining a playful and motivating atmosphere. Moreover, digital game activities promote collaboration and communication when used in group settings, fostering social and emotional growth. Despite their potential, challenges such as teacher preparedness, access to digital devices, and the need for safe and age-appropriate content must be addressed to ensure successful implementation. This article explores pedagogical foundations, benefits, and limitations of artificial intelligence-based digital game activities in preschool education, focusing on strategies for designing and integrating them into daily routines. Practical recommendations are provided to support educators in effectively using AI technologies as a means to enrich learning experiences and strengthen early childhood development.